Synergistic effect of compost and moringa leaf extract biostimulants on the remediation of gold mine tailings using chrysopogon zizanioides - Nkanyiso Mlalazi; Luke Chimuka; Mulala Danny Simatele (Scientific African, 2024)
Phytoremediation is a cost-effective and environmentally friendly method for restoring degraded land. However, optimizing phytoremediation conditions and using locally sourced materials can further improve the sustainability of this approach. A 3×2×2 factorial design was used in determining the optimal parameters in the remediation of gold mine tailings using vetiver grass. The treatments consisted of three compost concentrations (0 %, 30 % and 60 %), two biostimulant types (laboratory-extracted and commercial biostimulants) and two application regimens (once and twice a week) in a randomized complete block design. The biomass and metal concentrations in the vetiver grass were measured after 16 weeks. All the vetiver that was planted in 0 % compost amendment died within four weeks regardless the MLE treatment. There was no significant difference in vetiver biomass between vetiver grown in 30 % and that grown in 60 % compost amendment. Biostimulant application frequency led to no significant differences. A difference on vetiver biomass due to the type of moringa leaf extract was eminent, with laboratory moringa leaf extract resulting in significantly higher biomass in vetiver grown on 60 % compost yet the commercial moringa leaf extract producing significantly higher vetiver biomass on vetiver grown on 30 % compost amendment. These findings suggest that the optimal combination for field study would be 30 % compost amendment with commercial biostimulant for a more cost-effective option.